Skin Immune Response of Immunocompetent and Immunosuppressed C57BL/6 Mice After Experimental Subcutaneous Infection Caused by Purpureocillium lilacinum - Corrêa-Moreira, Danielly; dos Santos, Arethuza; Menezes, Rodrigo C.; Morgado, Fernanda N.; Borba, Cintia M.; Oliveira-Ferreira, Joseli (Frontiers in Microbiology, 2021)
Hyalohyphomycosis is a fungal infection characterized by the presence of a hyaline mycelium in the host. It is caused by several agents, such as Purpureocillium lilacinum. Our study aimed to evaluate the in situ immune response to subcutaneous hyalohyphomycosis by P. lilacinum in C57BL/6 murine models. The fungal isolate was inoculated in mice randomly distributed in immunocompetent/infected (CI) and immunosuppressed/infected (SI) groups. Mice were evaluated on days 1, 3, 5, and 7 after inoculation. Histopathological studies showed several lesions in the site of infection as well as the formation of multifocal and mixed inflammatory infiltrates, which differed between immunocompetent (CI) and immunosuppressed (SI) groups. This analysis also revealed conidia and hypha-like structures in subcutaneous tissues of mice of both groups. The immunohistochemical analysis showed lower percentages of macrophages and neutrophils in SI group compared to CI. Moreover, the intensity of IL-1 and nitric oxide synthase 2 production by cells of immunosuppressed mice was discrete, compared to immunocompetent mice that ranged from moderate to intense over time. The quantitative interference of dexamethasone in the response to the fungus was also demonstrated. We concluded that our results can be useful not only to broaden the knowledge on Purpureocillium lilacinum but also based on this host-parasite relationship, thus contributing to the understanding of the mechanisms of resistance and susceptibility.